Smoldering myeloma in a patient with B12 deficiency: The importance of appropriate differential diagnosis of peripheral plasma cells - Joaquín Jerez; Maria Perez-Rossi; Ana María Guzmán; Felipe Rojas (Archives of Hematology Case Reports and Reviews - Peertechz Publications, 2020)
A 79-year-old woman without relevant past medical history presented at Hospital Clínico UC Christus with progressive dyspnea and edema of lower extremities. Initial laboratory workup showed severe macrocytic anemia (hemoglobin, 5.7 gr/dL; MCV, 117 fL), associated with leukopenia (2800 uL), low platelet count (104000 x 103uL) and high levels of LDH (6500 UI/L). A direct visualization of blood film was performed, which evidenced macrocytosis (Figure 1A [Digital microscopy; Cellavision,×100 objective]), with ovalocytes and a few erythroblasts (Figure 1B),  hypersegmented neutrophils and eosinophils (Figure 1C-D); findings suggestive of megaloblastic anemia.